Development of Android GIS Applications for Mapping Clean Water Sources in Natural Resource Management in Disaster-Affected Areas - Rysa Sahrial; Samsul Aripin; Eva Susilawati; Emil Herdiana (Universitas Islam Indragiri, 2026)
This research was motivated by the post-disaster challenges faced by the people of Sarampad Village, Cugenang District, Cianjur Regency, after the 2022 earthquake, which severely damaged vital infrastructure and disrupted access to clean water. The lack of a systematic mapping system for clean water sources highlights the urgent need for technology-based solutions to support effective and sustainable water resource management. The study employed a software development method using an Agile Programming approach, allowing iterative development and adaptation based on user feedback. Data were collected through field surveys, interviews with local communities and village officials, and direct observations of clean water source conditions. The system was designed using the Unified Modelling Language (UML), and the Android application was developed with Flutter Dart via the Visual Studio Code platform. Application functionality was tested using the black-box testing method to ensure performance reliability. The developed Android-based GIS application successfully maps and visualizes clean water sources, providing users with accurate and accessible spatial information. The system enables communities to identify the nearest clean water sources efficiently, particularly in post-disaster conditions. The findings demonstrate that integrating GIS with mobile technology can significantly improve public access to clean water information while promoting community involvement in environmental resource management. This innovation serves as a practical step toward sustainable and participatory water resource management in disaster-affected areas.